Confocal laser endomicroscopy: a novel method for prediction of relapse in Crohn’s disease - Karstensen, John Gásdal; Săftoiu, Adrian; Brynskov, Jørn; Hendel, Jakob; Klausen, Pia; Cârtână, Tatiana; Klausen, Tobias Wirenfeldt; Riis, Lene Buhl; Vilmann, Peter (Endoscopy, 2016)
Background and study aims: Confocal laser endomicroscopy (CLE) has been shown to predict relapse in ulcerative colitis in remission, but little is currently known about its role in Crohn’s disease. The aim of this study was to identify reproducible CLE features in patients with Crohn’s disease and to examine whether these are risk factors for relapse.Patients and methods: This was a single-center prospective feasibility study of CLE imaging in patients with Crohn’s disease. CLE imaging was performed in the terminal ileum and four colorectal sites, and was correlated with histopathology and macroscopic appearance. Clinical relapse, defined as the need for treatment escalation or surgical intervention, was recorded during follow-up.Results: The study included 50 patients: 39 with Crohn’s disease (20 in remission), and 11 controls. Ileal fluorescein leakage and microerosions were significantly more frequent in patients with endoscopically active Crohn’s disease compared with patients with inactive Crohn’s disease and controls (P = 0.005 and (P = 0.006, respectively). The same applied to colorectal fluorescein leakage and vascular alterations ((P = 0.043 and (P = 0.034, respectively). During a 12-month follow-up period, ileal fluorescein leakage and microerosions were significant risk factors for relapse in the subgroup of patients in remission (log rank (P = 0.009 and (P = 0.007, respectively) as well as in the entire group of patients with Crohn’s disease (log rank (P = 0.006 and (P = 0.01, respectively). Inter- and intraobserver reproducibility was almost perfect (κ > 0.80) or substantial (κ > 0.60) for the majority of CLE parameters.Conclusions: CLE can identify reproducible microscopic changes in the terminal ileum that are risk factors for relapse in patients with otherwise inactive Crohn’s disease.Trial registration: ClinicalTrials.gov (NCT01738529).